1988
DOI: 10.2307/30144143
|View full text |Cite
|
Sign up to set email alerts
|

Stress Ulcer Prophylaxis and Ventilation Pneumonia: Prevention by Antibacterial Cytoprotective Agents?

Abstract: The gastric and tracheal flora of 142 consecutive patients receiving stress ulcer prophylaxis were investigated, identifying identical isolates by typing. Furthermore, the growth pattern of normal respiratory bacteria and organisms causing ventilation pneumonia at different pH values and the in vitro effect of sucralfate and bismuth subsalicylate on these bacteria in simulated gastric fluid were studied. The results obtained were as follows: (1) with rising gastric pH bacterial counts in gastric aspirates, esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
2

Year Published

1989
1989
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 27 publications
2
24
2
Order By: Relevance
“…However, our data do not support results from previous studies on intubated ICU patients, which suggested that gastric colonization was a significant risk factor for subsequent tracheal colonization or pneumonia [5,[8][9][10].…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…However, our data do not support results from previous studies on intubated ICU patients, which suggested that gastric colonization was a significant risk factor for subsequent tracheal colonization or pneumonia [5,[8][9][10].…”
Section: Discussioncontrasting
confidence: 57%
“…The results of this study confirm that intragastric microbial growth is pH-dependent [18][19][20] and promoted by treatment with Hs-receptor blockers or antacids [3][4][5][6][7][8]. However, our data do not support results from previous studies on intubated ICU patients, which suggested that gastric colonization was a significant risk factor for subsequent tracheal colonization or pneumonia [5,[8][9][10].…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations